Transcriptome Sequencing Identifies Novel Immune Response Genes Highly Related to the Severity of Human Adenovirus Type 55 Infection - Xu, Wen; Xu, Zhe; Huang, Lei; Qin, En-Qiang; Zhang, Jie-li; Zhao, Peng; Tu, Bo; Shi, Lei; Li, Wen-Gang; Chen, Wei-Wei (Frontiers in Microbiology, 2019)
Human adenovirus type 55 (HAdV-55) is considered a highly virulent pathogen causing severe and even deadly pneumonia in immunocompetent people. The mechanisms of HAdV-55-induced initiation and progression of severe pneumonia remain ambiguous. In the current study, we endeavored to identify novel immune genes which are substantially involved in the pathogenesis of severe inflammation in HAdV-55-infected patients. HAdV-55-infected patients with upper respiratory tract symptoms (minor patients) and pneumonia (severe patients) were enrolled. Through transcriptome sequencing and quantitative real-time PCR, the peripheral blood mononuclear cells of the patients were analyzed. We found that the expression of eight genes, including Il18, Il36b, Il17rc, Tnfsf10, Tnfsf11, Tnfsf14, Tnfsf15, and Il1a, were closely correlated with the severity of HAdV-55 infection. Most of these genes belong to interleukin-1 family or tumor necrosis factor (TNF) superfamily, respectively. The changes in gene expression were confirmed by Western blot assay. Our data will be crucial for deepening the understanding of the pathogenic mechanisms of severe pneumonia in HAdV-55 infection.